The role of community-based health planning and services strategy in involving males in the provision of family planning services: a qualitative study in Southern Ghana - Adongo, P.B.; Tapsoba, P.; Phillips, J.F; Tabong, P.T.; Stone, A.; Kuffour, E.; Esantsi, S.F.; Akweongo, P. (My University, 2013)
Abstract Background Reproductive health and Family Planning (FP) services have been of global concern especially in developing countries where fertility rates are high. Traditionally FP services had always targeted females with little or no attention given to males. To ensure equitable distribution of health services, Ministry of Health (MOH), Ghana adopted the Community-Based Health Planning and Services (CHPS) as a nationwide health policy with the aim of reducing obstacles to physical and geographical access to health care delivery including FP services. However, not much is known about the extent to which this policy has contributed to male involvement in FP services. This qualitative descriptive study was therefore designed to explore male involvement in FP services in communities with well functioning CHPS and those with less or no functioning CHPS structures. The study further solicited views of the community on the health status of children. Methods This was a qualitative descriptive study and adapted the design of an ongoing study to assess the impact of male involvement in FP referred to as the Navrongo experiment in Northern Ghana. Twelve focus group discussions were held with both male and female community members, six in communities with functional CHPS and six for communities with less/no-functional CHPS. In addition, fifty- nine (59) in-depth interviews were held with Community Health Officers (CHOs), Community Health Volunteers (CHVs) and Health Managers at both the districts and regional levels. The interviews and discussions were tape recorded digitally, transcribed and entered into QSR Nvivo 10© for analysis. Results The results revealed a general high perception of an improved health status of children in the last ten years in the communities. These improvements were attributed to immunization of children, exclusive breastfeeding, health education given to mothers on childcare, growth monitoring of children and accessible health care. Despite these achievements in the health of children, participants reported that malnutrition was still rife in the community. The results also revealed that spousal approval was still relevant for women in the use of contraceptives; however, the matrilineal system appears to give more autonomy to women in decision-making. The CHPS strategy was perceived as very helpful with full community participation at all levels of the implementation process. Males were more involved in FP services in communities with functioning CHPS than those without functioning CHPS. Conclusion The CHPS strategy has increased access to FP services but spousal consent was very important in the use of FP services. Involving males in reproductive health issues including FP is important to attain reproductive health targets.